Using the AAQ-II and the IRAP to predict the occurrence of experiential avoidance (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
The present study aimed to investigate whether two experiential avoidance measures, the AAQ-II and na IRAP, would predict the participant’s performance during an avoidance task. The procedure consisted of three phases: (1) answering questionnaires (including the AAQ-II); (2) responding an IRAP developed to assess EE; (3) responding to an avoidance test. Data collection was individualized. Adult participants composed two groups depending on their performance on the final task: Avoidance=0 (participants who did not emit any avoidance response during the test; n = 17) and Avoidance>2 (participants who emitted at least three avoidance responses; n = 18). There was no difference between groups regarding the AAQ-II scores. On the other hand, participants from the group Avoidance>2 responded faster to “true” on those IRAP trials that presented phases related to avoiding negative private events – compared to the group Avoidance=0. The effect of relational responding on the occurrence of EA is discussed.
Keywords: experiential avoidance; AAQ-II; IRAP; avoidance teste; adults